The culture of connectivity : a critical history of social media - Dijck, José van (Oxford University Press, 2013)
"Social media penetrate our lives: Facebook, YouTube, Twitter and many other platforms define daily habits of communication and creative production. This book studies the rise of social media, providing both a historical and a critical analysis of the emergence of major platforms in the context of a rapidly changing ecosystem of connective media. Author José van Dijck offers an analytical prism that can be used to view techno-cultural as well as socio-economic aspects of this transformation as well as to examine shared ideological principles between major social media platforms. This fascinating study will appeal to all readers interested in social media."-Resumé vydavatel
Keywords: internetové sociální sítě -- dějiny; sociální média -- dějiny; Internet social networks -- history; social media -- history; elektronické knihy; studie; electronic books; studies